A level up: Community seed banks in Nepal join forces - Shrestha, Pitambar; Clancy, Evelyn; Vernooy, Ronnie (2020)
Community seed banks in Nepal have a long and rich history, but it is only recently that they have come together to form the legally registered national Community Seed Banks Association of Nepal (CSBAN), probably the first such association anywhere in the world. CSBAN has developed an on-line seed catalogue of local varieties available from its members and accessible through a novel mobile app 'Our Seed'. In 2019, the Association organized two major seed fairs between communities to exchange seeds, planting materials and related knowledge. It has developed a novel method to categorize community seed banks using a five-star classification system, which aims to value, reward and encourage community seed banks to develop their capacities. The Association, with its vision of maintaining and harnessing Nepal’s rich agricultural biodiversity for human health and well-being, has been included in the Nepal Agriculture Research Council’s annual programme of work – an important recognition of its existence and efforts. CSBAN wishes to expand its activities to promote on-farm management of agricultural biodiversity and to develop a community seed bank self-financing mechanism, with a pilot on marketing of local produce. Joining forces has raised these Nepali community seed banks to a new level and they continue to inspire other community seed banks around the world.